Approaches and potentials for pool boiling enhancement with superhigh heat flux on responsive smart surfaces: A critical review. (March 2022) - Yuan, Xiao; Du, Yanping; Su, Jing
Abstract: The study concerns a comprehensive summarization in using hybrid or hierarchical structures with the adhesion of smart materials for enhancing the heat transfer coefficient (HTC) and critical heat flux (CHF) simultaneously in boiling phenomenon. A review of approaches for surface modifications to enhance the pool boiling heat transfer was conducted firstly. Specifically, these include modifications by fabrication of micro/nano structures, addition of micro/nano coatings or porous surfaces, or the combination of the above, which artificially optimize the wettability of the heated surface in advance of the boiling process. As a result, the design of hybrid surfaces can be optimized. Subsequently, great effort was put in introducing the recent development of smart surfaces fabricated by typical methods. The appliance of the smart materials can actively change the wettability characteristics of surfaces during the boiling process. On these basis, the potentials of the promising surface combining micro-nano scaled and wettability hybrid structures with smart materials was discussed. These include the evaluation of the maximum HTC and CHF that could be achieved, the advanced techniques for manufacturing the enhanced surfaces, and the extended applications in diverse fields for the achievement of super high heat flux transportation based on the combined smart surfaces. However, several vital challenges associated with smart surfaces need to be addressed. For example, the rigorous thermal conditions for the wettability transformation on metal oxide films, the weak mechanical property of switchable polymers, the cost and recovery ratio of shape memory alloys (SMAs), and the mismatch of temperature range for the wettability transition in the boiling process, etc. Nevertheless, suggestions have been given in this review to provide solutions in perspective of structure machining, materials selections and fabrication methods. Smart surfaces inspired from the natural environment can act as a crucial role in low carbon energy and environment applications. These include the anti-fogging, anti-icing, oil/water separation, drag-reduction and anti-corrosion for environment protecting, and power generation, anti-conditioning, thermal management, solar cells and nanogenerators for energy-saving purposes. Highlights: Super-high heat flux can be achieved on hierarchical smart surfaces combined with thermal-responsive materials. Optimization approaches, advanced fabrications and extended applications of hybrid smart surfaces have been analyzed. Suitable smart materials with temperature-dependent wettability need to be selected for the boiling enhancement. Smart surfaces fabricated with multifunctional properties exhibit a high potential in low carbon energy applications.